Role of Glycosylation/Deglycolysation Processes in Francisella tularensis Pathogenesis - Barel, Monique; Charbit, Alain (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis is able to invade, survive and replicate inside a variety of cell types. However, in vivo F. tularensis preferentially enters host macrophages where it rapidly escapes to the cytosol to avoid phagosomal stresses and to multiply to high numbers. We previously showed that infection of human monocytes by F. tularensis LVS triggered the deglycosylation of the glutamine transporter SLC1A5. However, this deglycosylation, specifically induced by Francisella infection, was not restricted to SLC1A5, suggesting that host protein deglycosylation processes in general might contribute to intracellular bacterial adaptation. Indeed, we later found that Francisella infection modulated the transcription of numerous glycosidase and glycosyltransferase genes in human macrophages and analysis of cell extracts revealed an important increase of N and O-protein glycosylation. In eukaryotic cells, glycosylation has significant effects on protein folding, conformation, distribution, stability and activity and dysfunction of protein glycosylation may lead to development of diseases like cancer and pathogenesis of infectious diseases. Pathogenic bacteria have also evolved dedicated glycosylation machineries and have notably been shown to use these glycoconjugates as ligands to specifically interact with the host. In this review, we will focus on Francisella and summarize our current understanding of the importance of these post-translational modifications on its intracellular niche adaptation.